Synthesis of intermetallic Ni3Al Alloy: properties and high temperature oxidation behavior - Ismail, Roslina; Yaacob, Iskandar Idris (Trans Tech Publications, Switzerland, 2010)
Two different methods were utilized to synthesize intermetallic nickel aluminide alloy. The first method was combination of powder metallurgy and reaction synthesis (IMC-RS) and the second method was plasma melting to form homogenous plasma melted samples (IMC-PM). XRD patterns for both samples showed complete formation of single phase Ni3Al. Saturation magnetization value for IMC-RS was 0.445 emu/g and IMC-PM was 0.157 emu/g. This was comparable with Ms value of commercial Ni3Al from Alfa Aeser (0.398 emu/g). The reduced elastic modulus, Er value of IMC-PM and IMC-RS were 441.09 MPa. 408.2 MPa respectively. Both samples were exposed to 1%SO2/air gas mixture at 1000°C for 24-hour duration. The isothermal kinetic results for both samples were parabolic indicating rate limiting step. The oxide scales consisted of NiO, NiAl2O4 and Al2O3. © (2010) Trans Tech Publications.